PERANAN SELF-ESTEEM TERHADAP CAREER DECISION MAKING SELF-EFFICACY PADA PELAJAR TINGKAT SMA DI TANGERANG - Oktafiansyah, Nico Surya; Monika , Monika (Provitae: Jurnal Psikologi Pendidikan, 2025)
Self-esteem is defined as how a person treats himself, both positively and negatively, as well as a person's assessment of his thoughts and feelings in totality concerning himself. Lack of self-confidence can have an impact on students' lives, especially on their education. Students who should be able to have self-confidence, enjoy new things, and be optimistic in achieving certain goals, instead find it difficult to define themselves, worried about trying new things because they imagine failure that might occur. High self-esteem means that your self-efficacy in making career choices will also be better, so that the possibility of continuing your life to the next level will be better with decisions made correctly. Because of this, the importance of high self-esteem means that your self-efficacy in determining career choices will also be better, and vice versa. If the level of self-esteem is low, then the ability of self-efficacy in determining career choices will also be low. This research uses quantitative methods and Google Forms to distribute questionnaires to participants. Participants for this research were 296 high school students in the Tangerang area. In this study, the measuring instruments used were the Rosenberg self-esteem Scale (RSES) and career decision making self-efficacy (CDMSE). The research results show that self-esteem has a positive influence on CDMSE.